Evaluation of a metalloporphyrin (THPPMnCl) for necrosis-affinity in rat models of necrosis. (26th November 2015) - Li, Yue; Liu, Xuejiao; Zhang, Dongjian; Lou, Bin; Peng, Fei; Wang, Xiaoning; Shan, Xin; Jiang, Cuihua; Gao, Meng; Sun, Ziping; Ni, Yicheng; Huang, Dejian; et al.
Abstract: The combination of an 13I I-labeled necrosis-targeting agent (NTA) with a vascular disrupting agent is a novel and potentially powerful technique for tumor necrosis treatment (TNT). The purpose of this study was to evaluate a NTA candidate, THPPMnCl, using 131 I isotope for tracing its biodistribution and necrosis affinity. 131 I-THPPMnCl was intravenously injected in rat models with liver, muscle, and tumor necrosis and myocardial infarction (MI), followed by investigations with macroscopic autoradiography, triphenyltetrazolium chloride (TTC) histochemical staining, fluorescence microscopy and H&E stained histology for up to 9 days. 131 I-THPPMnCl displayed a long-term affinity for all types of necrosis and accumulation in the mononuclear phagocytic system especially in the liver. Autoradiograms and TTC staining showed a good targetability of 131 I-THPPMnCl for MI. These findings indicate the potential of THPPMnCl for non-invasive imaging assessment of necrosis, such as in MI. However, 13I I-THPPMnCl is unlikely suitable for TNT due to its long-term retention in normal tissues.